Navigating the Archipelago City: everyday experiences and socio-political imaginaries of urban floods in Cartagena de Indias, Colombia - Silke Oldenburg; Laura Neville (Cahiers des Amériques Latines, 2021)
It is difficult to imagine the city of Cartagena de Indias, Colombia, the “Pearl of the Caribbean”, without water, as sandy beaches, lush mangrove forests, swampy landscapes and a maze of canals both surround the emblematic historic city centre and shape the expanding neighbourhoods in the so-called urban periphery. Water and the city are so closely intertwined that we introduce Cartagena as an Archipelago City to explore how urban residents navigate the city during seasonal urban rain and flooding. As climate change and rising sea level have become a pressing environmental challenge for coastal cities worldwide, we nuance mainstream discourses on governing and planning environmental futures by applying an actor-centred approach. We use navigation as an analytical lens, to provide insights into the way urbanites experience, anticipate and improvise around urban floods and imagine their city. Drawing on 13 months of ethnographic fieldwork in two distinct neighbourhoods, we dialectically explore how urban flooding slows down, disrupts and also speeds up Cartagena’s everyday life while its residents navigate their way through the Archipelago City. By arguing that these everyday experiences and imaginaries reflect the historical and social legacies of profound inequalities in the city, we are offering a window into the complex constituents of everyday social worlds that prevail in many Latin American coastal cities.